Selected Poems of Giovanni Pascoli - Pascoli, Giovanni, 1855-1912 (Book collections on Project MUSE., 2019)
The most comprehensive collection in English of the founder of modern Italian poetryGiovanni Pascoli (1855-1912)--the founder of modern Italian poetry and one of Italy's most beloved poets--has been compared to Robert Frost for his evocation of natural speech, his bucolic settings, and the way he bridges poetic tradition and the beginnings of modernism. Featuring verse from throughout his career, and with the original Italian on facing pages, Selected Poems of Giovanni Pascoli is a comprehensive and authoritative collection of a fascinating and major literary figure. Reading this poet of nature, grief, and small-town life is like traveling through Italy's landscapes in his footsteps--from Romagna and Bologna to Rome, Sicily, and Tuscany--as the country transformed from an agrarian society into an industrial one. Mixing the elevated diction of Virgil with local slang and the sounds of the natural world, these poems capture sense-laden moments: a train's departure, a wren's winter foraging, and the lit windows of a town at dusk. Incorporating revolutionary language into classical scenes, Pascoli's poems describe ancient rural dramas--both large and small--that remain contemporary. Framed by an introduction, annotations, and a substantial chronology, Taije Silverman and Marina Della Putta Johnston's translations render the variety, precision, and beauty of Pascoli's poetry with a profoundly current vision.